2005
DOI: 10.1002/adem.200500025
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Damage of Spark Plug Electrodes

Abstract: Knowledge about the erosion mechanisms of spark plug materials is of fundamental interest for the development of materials with a high resistance against electrode erosion. Endurance tests were performed to study the wear behaviour of platinum, iridium, silver and nickel as electrode materials for spark plugs between 200 and 900 °C. Oxidation must be the dominating mechanism, irrespective of the material. Additional calculations resulted in the suggestion of a plasma‐assisted oxidation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…[1][2][3] Arcs are known to be electrical discharges between two electrodes that can occur in gas or vacuum. 1,3, 4 The end result of arcs is surface damage that is often harmful, as in the case of linear collider components, 5 fusion reactors, 6 or spark plugs for cars, 7 but is also utilized for electrical discharge machining of materials. 8 The science behind arcing is surprisingly poorly understood, considering how widely they occur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Arcs are known to be electrical discharges between two electrodes that can occur in gas or vacuum. 1,3, 4 The end result of arcs is surface damage that is often harmful, as in the case of linear collider components, 5 fusion reactors, 6 or spark plugs for cars, 7 but is also utilized for electrical discharge machining of materials. 8 The science behind arcing is surprisingly poorly understood, considering how widely they occur.…”
Section: Introductionmentioning
confidence: 99%
“…1,7,9,10 It still remains unclear which ones are truly active and what is their range of applicability. 7 Understanding the mechanism is crucial for guiding the choice of materials for new high-gradient accelerator concepts and fusion reactors.…”
Section: Introductionmentioning
confidence: 99%
“…This is in support of the oxidation mechanism [12] which excludes particle ejection as contributor to electrode wear caused during an endurance test. Consequently, the viscosity cannot be accounted for the different erosion volumes measured, as this model is based on the particle ejection mechanism.…”
Section: Discussion Of the Wear Behaviourmentioning
confidence: 82%
“…[9,10] On the other hand, the large atomic weight of the oxides, especially of rare earth metals, leads to a reduced sputter rate during the glow discharge. [11] In a previous paper [12] we showed that oxidation plays a dominant role in the erosion of electrode materials. In the case of platinum, erosion stems from the plasma-assisted formation of volatile oxides in the cathode spot.…”
mentioning
confidence: 99%
“…In a different field of application it was shown that the addition of oxide materials improves the erosion resistance of spark plug electrodes because oxidation seems to play a major role as erosion mechanism [3,4]. An additional benefit is the reduced amount of platinum needed per unit volume of the electrode tip.…”
Section: Introductionmentioning
confidence: 99%